Colombian university journalism as a virtual stage for transitions toward acts of memory and peace - Rendon Cardona, Paula Andrea; Rivera Henao, Mauricio; Betancurth Becerra, Carlos Mario; Aristizábal, Cesar Alberto; Páez Valdéz, Julián Enrique (Frontiers in Education, 2022)
This article is concerned with narrating the research-creation experience that emerged from the CAPAZ project (Analytical Center for University Productions in the Framework of Conflict) and aims to account for the emergence of the transmedia web platform "RUTAS: University Peace Stories in Colombia," based on the analysis of the media representations of a sector of national opinion, specifically university journalism concerning peace narratives in the period 2000 to 2021. The proposal of a mixed methodological approach and an experimental scheme with Big Data techniques implied an automated lexicometric analysis leading to the application of a strategy for creating pedagogical narratives to order the results obtained. From the above, RUTAS was born as an exercise involving the deployment of knowledge and creative skills around design as a possibility and hypermediality as a scenario of digital and interactive stories, housed in a virtual, cultural, and open platform that would give rise to the various representations and media appropriations in the field of communication and education.